Weak and strong convergence theorems for zero points of inverse strongly monotone mapping and fixed points of quasi-nonexpansive mappings in Hilbert space - Buris Tongnoi (2020)
© 2019 by the Mathematical Association of Thailand. All rights reserved. In this paper, we propose a new algorithm for zero points of inverse strongly monotone mapping and fixed points of a finite of quasi-nonexpansive mappings in Hilbert space and prove weak and strong convergence theorems for the proposed methods under some conditions. Moreover, we also show that the sequence generated by our algorithm converges to a solution of some variational inequality problem.